French Language Interference In English For Specific Purposes Use: Interlingual Errors Among Electronics And Automation Students - Naima Khetir (The Journal of Studies in Language, Culture and Society, 2025)
This study examines the influence of the French language on the use of English for Specific Purposes (ESP) among engineering students. ESP learners are increasingly in need of English performance at both written and oral levels. Hence, French, a means of instruction, can have an impact on the English language practice. Therefore, the French language interference can occur in different English language use situations. This work sheds some light on interference errors that occur among sixty-nine engineering students while dealing with English in class. It also focuses on the possible frequency of interference misuse. This study was based on discovery approach. To tackle this issue, participants were asked to read a series of words while being recorded and were required to spot mistakes in items that contained grammatical, orthographic as well as lexical errors. A chart was designed to compare the frequency and the type of errors in both oral (phonological) and written forms. The analysis of the results showed that the students made a significant number of interference errors at different levels stated above. The lexical test registered the highest number of non-identification of errors. Hence, the role of the French language interference in ESP learning is considered rather facilitative for Algerian students.